Potential biodegradable face mask to counter environmental impact of Covid-19 - (:unkn) unknown (My University, 2021)
On the eve of the outbreak of the COVID-19 pandemic, there is a tremendous increase in the production of facemasks across the world. The primary raw materials for the manufacturing of the facemasks are non-biodegradable synthetic polymers derived from petrochemicals. Disposal of these synthetic facemasks increases waste-load in the environment causing severe ecological issues for flora and fauna. The synthesis processes of the polymers from the petrochemical by-products were also not eco-friendly, which releases huge greenhouse and harmful gases. Therefore, many research organizations and entrepreneurs realize the need for biodegradable facemasks to render similar performance as the existing non-biodegradable masks. The conventional textile fabrics made of natural fibers like cotton, flax, hemp, etc., can also be used to prepare facemasks with multiple layers in use for general protection. Such natural textile masks can be made anti-microbial by applying various herbal anti-microbial extracts like turmeric, neem, basil, aloe vera, etc. As porosity is the exclusive feature of the masks for arresting tiny viruses, the filter of the masks should have a pore size in the nanometre scale, and that can be achieved in nanomembrane manufactured by electrospinning technology. This article reviews the various scopes of electrospinning technology for the preparation of nanomembrane biomasks. Besides protecting us from the virus, the biomasks can be useful for skin healing, skincare, auto-fragrance, and organized cooling which are also discussed in this review article.
Keywords: Facemask; Biopolymers; Biodegradable; Bioextracts; Biomask; Respirator